2020
DOI: 10.1002/wrna.1634
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping mechanisms of lncRNA and expanded microsatellite RNA

Abstract: RNA has major regulatory roles in a wide range of biological processes and a surge of RNA research has led to the classification of numerous functional RNA species. One example is long noncoding RNAs (lncRNAs) that are structurally complex transcripts >200 nucleotides (nt) in length and lacking a canonical open reading frame (ORF). Despite a general lack of sequence conservation and low expression levels, many lncRNAs have been shown to have functionality in diverse biological processes as well as in mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 132 publications
0
8
0
Order By: Relevance
“…Regarding putative perturbations in raceRNA crosstalk and relevance of miRNA sponging in the pathogenesis of DM, further studies are needed to explain whether the presence of expanded repeats and aberrant expression of certain ceRNAs are interrelated. Interestingly, it was recently reported that functional mechanisms of lncRNAs and the potential pathogenic mechanisms of expanded microsatellite RNA may be linked [ 9 ]. Shared mechanisms include protein sequestration, peptide translation, miRNA processing and miRNA sequestration.…”
Section: Current Understanding Of the Activity Of Cernas In Dms And Directions For Further Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding putative perturbations in raceRNA crosstalk and relevance of miRNA sponging in the pathogenesis of DM, further studies are needed to explain whether the presence of expanded repeats and aberrant expression of certain ceRNAs are interrelated. Interestingly, it was recently reported that functional mechanisms of lncRNAs and the potential pathogenic mechanisms of expanded microsatellite RNA may be linked [ 9 ]. Shared mechanisms include protein sequestration, peptide translation, miRNA processing and miRNA sequestration.…”
Section: Current Understanding Of the Activity Of Cernas In Dms And Directions For Further Researchmentioning
confidence: 99%
“…There is growing evidence that, in pathology, the RNA communication system is disrupted [ 2 , 4 , 5 , 6 , 7 , 8 ]. It was also suggested that such communication between RNA molecules may play an important role in various repeat-associated diseases [ 9 , 10 ]. The common denominator of the repeat-associated diseases is a special mutation in relevant genes, where short nucleotide sequences are repeated many times and form unusually long tracts of repeats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeats as DNA can inhibit transcription of repeat-containing genes and promote the DNA damage response through R-loop formation (Tuduri et al 2009;Reddy et al 2011;Reddy et al 2014;Groh et al 2014;Haeusler et al 2014). Repeats as RNA can functionally sequester both canonical and non-canonical RNA binding proteins and prevent them from performing their normal functions (Miller et al 2000;Mankodi et al 2000;Jin et al 2007;Cooper-Knock et al 2014;Conlon et al 2016;Lee et al 2013; reviewed in Rodriguez and Todd 2019;Swinnen, Robberecht, and Van Den Bosch 2020;Johnson and Cooper 2021). Repeats can also be translated into toxic proteins, either via canonical translation (as occurs for a number of polyglutamine expansions) or via repeat associated non-AUG (RAN) initiated translation (Zu et al 2011;Todd et al 2013;Green et al 2017;Kearse et al 2016;Paulson et al 1997;Trottier et al 1995;La Spada et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…These foci are thought to represent repeat RNAs coassociated with specific RNA binding proteins, although they may also arise from intraand inter-molecular RNA-RNA interactions via RNA gelation (Jain and Vale 2017;Fay, Anderson, and Ivanov 2017;Mankodi et al 2001;Fardaei et al 2002;Tassone, Iwahashi, and Hagerman 2004;Iwahashi et al 2006;Jin et al 2007;Sofola et al 2007;Sellier et al 2010;Sellier et al 2013;Bajc Cesnik et al 2019). The exact behavior, biophysical properties, and associated protein and RNA factors of these RNA condensates varies across different repeat expansions (reviewed in Nussbacher et al 2019; Echeverria and Cooper 2012;Johnson and Cooper 2021). Traditionally, these foci are visualized by fluorescent in situ hybridization (FISH) ( Figure 1A) (Urbanek and Krzyzosiak 2016;Lee et al 2013;Urbanek, Michalak, and Krzyzosiak 2017;Hoem et al 2011;Verma et al 2019;Jin et al 2007).…”
Section: Introductionmentioning
confidence: 99%